A new process for sustainable wastewater treatment in Chilean copper smelters - Hansen, Henrik K.; Rojo, Adrián; Gutiérrez, Claudia (European Journal of Sustainable Development, 2016)
An actual Chilean copper smelter wastewater treatment is a complex process that actually mostly is focused on fulfillment of threshold values more than sustainability. The actual wastewater treatment includes a number of precipitation, neutralization, clarifying and filtering steps. This manuscript proposes a new sustainable process that would eliminate/reduce several of the disadvantages in an actual copper wastewater treatment such as a) reduced lime addition, b) a separate gypsum and heavy metal/arsenic precipitation, c) an electrodialysis stage that would recover copper, d) an easier ferric ion dosage for arsenic removal by electrocoagulation, and e) a less reagent consuming neutralization step. Keyword: Sustainable wastewater treatment, Electrocoagulation, Arsenic removal, Copper recovery